First report and genetic characterization of the highly pathogenic avian influenza A(H5N1) virus in Cabot's tern (Thalasseus acuflavidus), Brazil - Dilmara Reischak; Anselmo Vasconcelos Rivetti, Jr; Juliana Nabuco Pereira Otaka; Christian Steffe Domingues; Talita de Lima Freitas; Fernanda Gomes Cardoso; Lucas Oliveira Montesino; Ana Luiza Savioli da Silva; Fernanda Malta; Deyvid Amgarten; Aristóteles Goés-Neto; Antônio Fonseca de Oliveira, Júnior; et al. (Veterinary and Animal Science, 2023)
In 2021, the H5N1 virus lineage 2.3.4.4b spread to the Americas, causing high mortality in wild and domestic avian populations. South American countries along the Pacific migratory route have reported wild bird deaths due to A/H5Nx virus since October 2022. However, limited genomic data resulted in no cases reported in Brazil until May 2023.Brazil reported its first case of highly pathogenic avian influenza virus (HPAI A/H5N1) in May 2023. The virus was detected in Cabot's tern specimen in Marataízes, Espírito Santo. Cases were also found in backyard poultry and other wild birds, but no human or commercial poultry cases occurred. HPAI poses risks to the poultry industry, food security, and public health.Researchers used next-gen sequencing and phylogenetic analysis to study the Brazilian sample. It confirmed its affiliation with the 2.3.4.4b clade and proximity to sequences from Chile and Peru.This sheds light on the spread and evolution of HPAI A/H5N1 in the Americas, emphasizing continuous monitoring to mitigate risks for both avian and human populations. Understanding the virus's genetics and transmission allows implementing effective control measures to protect public health and the poultry industry.